Penerapan Good Governance pada Kepengurusan Pondok Pesantren Putri Al-Amien - Surur, Agus Miftakus; Cholifah, Kharisma Nur (Universitas Islam Negeri Raden Intan Lampung, 2018)
Good governance is the way in organizing resources and solve the problems of the public. Good governance arose due to dissatisfaction on the performance of Government organizer of public affairs. Good governance is needed in seeking and maintaining a social life, respect of the rights and obligations of every Member of society to realize. Boarding schools are also included in community groups. Each boarding schools must have had the caregiver, the organizational structure, students, and the code of conduct as well as the conditions that must be observed. There has to be cooperation from all parties so that community life created an orderly and harmonious. So, the principles of good governance should be applied in the system of governance. In this study, using this type of qualitative research. While the approach used, namely the approach of case studies. This type of approach to study intensively on one object of study it as a case that is about the application of good governance on boarding schools Daughter Al-Amien. As a result, the organizational system in boarding schools Daughter Al-Amien looks pretty good. Stewards still provide leniency on students to voice your opinions and defend themselves. Participation and responsibilities of students themselves as a society have also been quite good. The Naat dare infringe but remain ready to accept any consequences.